السلطة الإدارية المركزية في النظام الإداري الجزائري - حمزة كحلوش (My University, 2018)
Summary: Algeria's administrative management is consistent with the situation in various other States. It is based on the existence of a decentralized administration along with the central administration or what is termed in the jurisprudence of administrative law: "Central administrative authority", because of the difficulty of applying either system independently of the other. The central administrative authority consists of the constituent units of the executive branch: the Presidency of the Republic and the Government. Since the 1989 Constitution, the Algerian constitutional founder has adopted the principle of duality or dual membership of the executive branch and has formed two separate institutions: The Office of the President of the Republic, on the one hand, and the Government, on the other hand, and its functional unification by delegating authority to the effective exercise of the President of the Republic The Government, on the one hand, operates under its authority and, on the other hand, is accountable to it and to Parliament. Which leads us to say that the executive branch of the Algerian system is its body in the parliamentary system, which is based on the principle of duplication of executive power, In view of the constitutional privilege enjoyed by the President of the Republic in Algeria's political and administrative systems from the promulgation of the 1963 Constitution until the last constitutional amendment of 2016, he headed it. and confirmed by the presidential exercise of power, which settled on the appointment of the Chief Minister and the termination of his functions without any consideration for his political or party affiliation, taking into account the consultation of the parliamentary majority in the legislative institution, If that was a mere formality, leaving the discretion of the President to adopt In the opinion rendered or not taken. This situation clearly demonstrates that the President's institution is the original actor and controller of the State in general, and the administrative function in particular, and that it is the true practitioner of it through the legal status and powers conferred by the Constitution, as well as through the practice on which State administration methods have been established in the Algerian administrative system. ....................... ملخص : جاء التنظيم الإداري في الجزائر على نسق ما هو عليه الوضع في مختلف الدول الأخرى، إذ يقوم على وجود إدارة لامركزية إلى جانب الإدارة المركزية أو ما يصطلح عليها في فقه القانون الإداري: "بالسلطة الإدارية المركزية "، وذلك لصعوبة تطبيق أي من النظامين على حدى بشكل مستقل عن الآخر، إذ تتشكل السلطة الإدارية المركزية من الوحدات المكونة للسلطة التنفيذية والمتمثلة في: رئاسة الجمهورية والحكومة. حيث تبنى المؤسس الدستوري الجزائري مبدأ ازدواجية أو ثنائية السلطة التنفيذية عضويا، وذلك منذ صدور دستور 1989 ، وأسس لتكوينها من مؤسستين منفصلتين هما: رئاسة الجمهورية من جهة، والحكومة من جهة ثانية، وتوحيدها وظيفيا من خلال إسناد سلطة الممارسة الفعلية لرئيس الجمهورية، أما الحكومة فهي تعمل تحت سلطته، كما أنها مسؤولة أمامه من ناحية وأمام البرلمان من ناحية أخرى، الأمر الذي يدفعنا إلى القول بأن السلطة التنفيذية في النظام الجزائري جسمها في النظام البرلماني الذي يقوم على مبدأ إزدواجية السلطة التنفيذية، ورأسها في النظام الرئاسي وهذا بالنظر إلى الامتياز الدستوري الذي يتمتع به رئيس الجمهورية في النظامين السياسي والإداري الجزائريين وذلك منذ صدور دستور 1963 إلى غاية التعديل الدستوري الأخير لسنة 2016 ، والذي أكدته الممارسة الرئاسية للسلطة، والتي إستقرت على تعيين الوزير الأول وانهاء مهامه دون أي إعتبار لإنتمائه السياسي أوالحزبي، مع مراعاة استشارة الأغلبية البرلمانية في المؤسسة التشريعية، وان كان ذلك مجرد إجراء شكلي مع ترك السلطة التقديرية لرئيس الجمهورية في الأخذ بالرأي الصادر أوعدم الأخذ به. إن هذه الوضعية تبين بشكل قاطع أن مؤسسة الرئاسة هي الفاعل الأصلي والمتحكم في دواليب الدولة عامة، والوظيفة الإدارية خاصة، وأنها الممارس الحقيقي لها من خلال ما يمنحه الدستور لها من مراكز قانونية وصلاحيات، وكذا من خلال الممارسة التي استقرت عليها أساليب إدارة الدولة في النظام الإداري الجزائري. ........................ Résumé : La gestion administrative de l’Algérie est cohérente avec la situation dans divers autres États. Elle est basée sur l’existence d’une administration décentralisée avec l’administration centrale ou ce qui est appelé dans la jurisprudence du droit administratif : "autorité administrative centrale", en raison de la difficulté d’appliquer l’un ou l’autre système indépendamment de l’autre. L’autorité administrative centrale se compose des unités constitutives du pouvoir exécutif : la présidence de la République et le gouvernement. Depuis la Constitution de 1989, le fondateur constitutionnel algérien a adopté le principe de dualité ou de double appartenance au pouvoir exécutif et a formé deux institutions distinctes : le Bureau du Président de la République, d’une part, et le Gouvernement, d’autre part, et son unification fonctionnelle par délégation de pouvoir à l’exercice effectif du Président de la République Le Gouvernement, d’une part, fonctionne sous son autorité et, d’autre part, est responsable devant lui et devant le Parlement. Ce qui nous amène à dire que le pouvoir exécutif du système algérien est son organe dans le système parlementaire, qui repose sur le principe de duplication du pouvoir exécutif, Au vu du privilège constitutionnel dont jouissait le Président de la République dans les systèmes politiques et administratifs algériens depuis la promulgation de la Constitution de 1963 jusqu’à la dernière modification constitutionnelle de 2016, il le dirigeait. et confirmé par l’exercice du pouvoir présidentiel, qui a décidé de la nomination du ministre en chef et de la cessation de ses fonctions sans aucune considération pour son affiliation politique ou partisane, tenant compte de la consultation de la majorité parlementaire au sein de l’institution législative, S’il s’agissait d’une simple formalité, il appartient au Président d’adopter Dans l’opinion rendue ou non prise. Cette situation démontre clairement que l’institution du Président est l’acteur originel et le contrôleur de l’État en général, et la fonction administrative en particulier, et qu’il en est le véritable praticien par le statut juridique et les pouvoirs conférés par la Constitution, ainsi que par la pratique sur laquelle les méthodes d’administration de l’État ont été établies dans le système administratif algérien.